IMPLEMENTASI KEBIJAKAN KETERBUKAAN INFORMASI PUBLIK DI PEMERINTAHAN KABUPATEN SIAK - Angga Pratama; Sujianto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
This research was conducted with limitations in the form of policy implementation and factors that influence the policy to know the implementation of public information disclosure policies and the inhibiting factors in the Siak Regency Government. The research was conducted using a qualitative method with a case study approach. The results of the study indicate that the implementation of the Public Information Disclosure Policy in the Siak Regency Government has not been optimal or well realized. The factors that cause this to happen are the lack of coordination between the government and the community as well as social conditions. Based on these findings, implementors should improve their coordination with related agencies, provide strict sanctions against persons who do not comply with applicable regulations, and improve facilities in the form of health insurance to seek information through information portals. This effort is made to create a more informative government so that people are more concerned with their government following the expectations of the Siak Regency government. Keywords: policy, public information disclosure, government, Siak Regency